Blood pressure, heart rate and tubuloglomerular feedback in A1AR‐deficient mice with different genetic backgrounds. (24th September 2014) - Kim, S. M.; Mizel, D.; Qin, Y.; Huang, Y.; Schnermann, J.
Abstract Aim Differences in genetic background between control mice and mice with targeted gene mutations have been recognized as a potential cause for phenotypic differences. In this study, we have used A1AR‐deficient mice in a C57Bl/6 and SWR/J congenic background to assess the influence of background on the effect of A1AR‐deficiency on cardiovascular and renal functional parameters. Methods In A1AR+/+ and A1AR−/− mice in C57Bl/6 and SWR/J congenic backgrounds, we assessed blood pressure and heart rate using radio‐telemetry, plasma renin concentrations and tubuloglomerular feedback. Results We did not detect significant differences in arterial blood pressure (MAP) and heart rates (HR) between A1AR+/+ and A1AR−/− mice in either C57Bl/6, SWR/J or mixed backgrounds. MAP and HR were significantly higher in SWR/J than in C57Bl/6 mice. A high NaCl intake increased MAP in A1AR−/− mice on C57Bl/6 background while there was less or no salt sensitivity in the SWR/J background. No significant differences in plasma renin concentration were detected between A1AR−/− and A1AR+/+ mice in any of the strains. Tubuloglomerular feedback was found to be absent in A1AR−/− mice with SWR/J genetic background. Conclusions While this study confirmed important differences between inbred mouse strains, we did not identify phenotypic modifications of A1AR‐related effects on blood pressure, heart rate and plasma renin by differences in genetic background.